COMPOSTING: AN ECO-FRIENDLY SOLUTION FOR ORGANIC WASTE MANAGEMENT TO MITIGATE THE EFFECTS OF CLIMATE CHANGE - HASSAN, NADA YASSER IBRAHIM; EMAN YEHIA MOHAMED BADAWI; DINA ESSAM ABO SREA MOSTAFA (Innovare Journal of Social Sciences, 2023)
Composting is the process of converting organic waste into a nutrient-rich soil amendment. It is an eco-friendly and sustainable way to manage organic waste and it can have a number of benefits for the environment. Composting can help to reduce greenhouse gas emissions, improve soil quality, and conserve water. It can also help to reduce the amount of waste that goes to landfills, which can help to protect human health and the environment. The inputs of waste for composting can include food scraps, yard waste, and other organic materials. These materials are broken down by microorganisms in a process called decomposition. There are a lot of decomposition technologies as not limited to, aerobic decomposition which requires oxygen, so it is important to turn the compost pile regularly to ensure that there is enough oxygen present. The processes used in composting can vary depending on the scale of the operation. However, all composting methods involve the following steps: Collection of organic waste, followed by preparation of the waste (e.g., shredding and chopping), then mixing of the waste with other materials (e.g., soil, sand, and micro-organisms), turning of the compost pile, then, monitoring of the compost pile (e.g., moisture content, and temperature), and finally, harvest of the compost. The outputs of composting are a nutrient-rich soil amendment called compost. Compost can be used to improve soil quality, increase crop yields, and reduce the need for chemical fertilizers. Compost can also be used to create a more sustainable landscape by reducing the need for imported topsoil. This review will discuss the benefits of composting and how it can be used to mitigate the effects of climate change. It will also provide information on how to start composting and the different types of composting systems and factors affecting the compositing process that are available.